Beliefs, attitudes and practices related to saving water and electricity in households in the Valle de Aburrá - Mejía-Durango, Diana Patricia; Serna-Monterrosa, Melissa; Córdoba-Castillo, Gustavo; González-Suárez, Mateo; Salas-Zapata, Walter Alfredo (Revista Colombiana de Ciencias Sociales, 2026)
Introduction: Consumer behavior is an understudied determinant of residential water and electricity demand and, when it is studied, capturing and quantifying it is often problematic due to the absence of validated scales. Objective: to describe the beliefs, attitudes and practices related to water and electricity saving in households in the Aburrá Valley, with the purpose of contributing to the construction of scales that allow the study of saving behavior. Method: qualitative research with particularistic ethnography. Results and discussion: households have two types of beliefs (about consumption and about saving strategies), three types of attitudes (attitude toward consumption practices, emotional responses to saving behavior, and concern and feeling of responsibility for the environmental consequences of consumption) and three types of practices (investment in efficient technologies, water collection and reuse, and restriction of consumption practices). These findings constitute a basis for the development of a comprehensive scale that allows the quantification of the different dimensions of behavior and that has better validity characteristics than the instruments currently in use.